An Improved Protection Of High Voltage Air Line Using Differential Relays - Ariyanto Gultom; Parlin Siagian; Amani Darma Tarigan (Jurnal Scientia, 2024)
A static electrical device is like a power transformer, one of the functions of which is to transfer one power circuit to another circuit, either changing the voltage without having to change the frequency. This paper described a Protection is a system in electricity and has a function as an isolate, breaker and separator if there is a disturbance. The working principle of the differential relay is to compare the vector I1 of the primary side current with I2 of the secondary side current. "The results of the mathematical calculation of the setting current for the differential current obtained are 0.0961865394 A and this is different from the setting current installed in the differential relay on the power transformer of 1 substation, namely 0.3 A."